Analysis of StudentÔÇÖs Writing Which Reflect Ghost Stories in Indonesian Horror Film - Ratmiati, Ratmiati; Muspardi, Muspardi; Domi Fella Henanggil, Mita; Antoni, Sri (Universitas Islam negeri Mahmud Yunus Batusangkar, 2024)
Horror films circulating in Indonesia today can be watched by anyone from various social media, including underage elementary school students. As a result of watching this horror film, students often fantasize and imagine everything must be scary and scary. Even students will also write stories about that scary thing in the assignment given by the teacher. This study aims to analyze writings made by elementary school students that reflect horror stories in Indonesian horror films. The subjects of the study were 31 students of SD 05 Nagrek with works containing ghost stories whose contents were almost the same as ghost stories in Indonesian horror films. Research is descriptive qualitative research with observation, interview, documentation methods. The data analysis technique used is the theory of Miles and Huberman which is carried out by means of (1) Data reduction (2) Data presentation (3) Conclusion drawing and verification. Checking the validity of data is carried out by extending observations and triangulation. The triangulation used in this study is source triangulation which is done by checking data that has been obtained through several sources. The results showed that (1) half of the 31 students wrote stories with content that was almost similar to ghost stories filmed in Indonesia. (2) Students get ideas in writing ghost stories from watching themselves, told by friends and just imagining.┬á┬á